Worldwide version-controlled database of glacier thickness observations - Welty, Ethan; Zemp, Michael; Navarro, Francisco; Huss, Matthias; Fürst, Johannes; Gärtner-Roer, Isabelle; Landmann, Johannes; Machguth, Horst; Naegeli, Kathrin; Andreassen, Liss M.; Farinotti, Daniel; Li, Huilin (Earth System Science Data, 2020)
Although worldwide inventories of glacier area have been coordinated internationally for several decades, a similar effort for glacier ice thicknesses was only initiated in 2013. Here, we present the third version of the Glacier Thickness Database (GlaThiDa v3), which includes 3 854 279 thickness measurements distributed over roughly 3000 glaciers worldwide. Overall, 14% of global glacier area is now within 1 km of a thickness measurement (located on the same glacier) - a significant improvement over GlaThiDa v2, which covered only 6% of global glacier area and only 1100 glaciers. Improvements in measurement coverage increase the robustness of numerical interpolations and model extrapolations, resulting in better estimates of regional to global glacier volumes and their potential contributions to sea-level rise. In this paper, we summarize the sources and compilation of glacier thickness data and the spatial and temporal coverage of the resulting database. In addition, we detail our use of open-source metadata formats and software tools to describe the data, validate the data format and content against this metadata description, and track changes to the data following modern data management best practices. Archived versions of GlaThiDa are available from the World Glacier Monitoring Service (e.g., v3.1.0, from which this paper was generated: https://doi.org/10.5904/wgms-glathida-2020-10; GlaThiDa Consortium, 2020), while the development version is available on GitLab (https://gitlab.com/wgms/glathida, last access: 9 November 2020).
CRIS-Team Scopus Importer:2020-12-11